A multicenter phase II study on the efficacy and safety of hetrombopag in patients with severe aplastic anemia refractory to immunosuppressive therapy. (March 2022) - Peng, Guangxin; He, Guangsheng; Chang, Hong; Gao, Sujun; Liu, Xinjian; Chen, Tong; Li, Pei; Han, Bing; Miao, Miao; Ge, Zheng; Ge, Xiaoyan; Li, Fei; et al.
Background: In this single-arm phase II study (NCT03557099), we evaluated the efficacy and safety of hetrombopag, a small molecule thrombopoietin (TPO) receptor agonist, in patients with severe aplastic anemia (SAA) who were refractory to standard first-line immunosuppressive therapy (IST). Methods: SAA patients who were refractory to standard first-line IST were given hetrombopag orally at an initial dose of 7.5 mg once daily to a maximum of 15 mg once daily, for a total of 52 weeks. The primary endpoint was proportion of patients achieving hematologic responses in ⩾1 lineage at week 18. Results: A total of 55 eligible patients were enrolled and received hetrombopag treatment. This study met its primary endpoint, with 23 [41.8%, 95% confidence interval (CI) = 28.7–55.9] patients achieving hematologic response in ⩾1 lineage at week 18 after initiation of hetrombopag treatment. Twenty-four (43.6%, 95% CI = 30.3–57.7) and 27 (49.1%, 95% CI = 35.4–62.9) of the 55 patients responded in ⩾1 lineage at weeks 24 and 52, respectively. Median time to initial hematologic response was 7.9 weeks (range = 2.0–32.1). The responses were durable, with a 12-month relapse-free survival rate of 82.2% (95% CI = 62.2–92.2). Adverse events occurred in 54 (98.2%) patients, and 28 (50.9%) patients had treatment-related adverse events. Seventeen (30.9%) patients had adverse events of grade ⩾3. Serious adverse events occurred in 15 (27.3%) patients and three deaths (5.5%) were reported. Conclusion: Hetrombopag showed encouraging efficacy with durable hematologic responses in patients with SAA who were refractory to IST. Hetrombopag was well tolerant and safe for long-term use. ClinicalTrials.gov identifier: NCT03557099